The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cbic.202100283
|View full text |Cite
|
Sign up to set email alerts
|

Sphaeropsidin A: A Pimarane Diterpene with Interesting Biological Activities and Promising Practical Applications

Abstract: Sphaeropsidin A (SphA) is a tetracyclic pimarane diterpene, first isolated as the main phytotoxin produced by Diplodia cupressi the causal agent of a severe canker disease of Italian cypress (Cupressus sempervirens L.). It was also produced, together with several analogues, by different pathogenic Diplodia species and other fungi and showed a broad array of biological activities suggesting its promising application in agriculture and medicine. The anticancer activity of SphA is very potent and cell specific. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interestingly, Sphs A, B and C were detected in all the investigated crude extracts. Considering that Sph A and its analogues are already known to be the main phytotoxins produced by Diplodia species [24], we conjectured that these members of the family of tetracyclic pimarane diterpenes could also be involved in the different virulence degrees observed in the strains of D. corticola from oaks investigated in this study. For this reason, Sphs A and B were selected to evaluate quantitative differences among the strains.…”
Section: Qualitative and Quantitative Analyses Of Secondary Metabolitesmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, Sphs A, B and C were detected in all the investigated crude extracts. Considering that Sph A and its analogues are already known to be the main phytotoxins produced by Diplodia species [24], we conjectured that these members of the family of tetracyclic pimarane diterpenes could also be involved in the different virulence degrees observed in the strains of D. corticola from oaks investigated in this study. For this reason, Sphs A and B were selected to evaluate quantitative differences among the strains.…”
Section: Qualitative and Quantitative Analyses Of Secondary Metabolitesmentioning
confidence: 88%
“…During a study on Botryosphaeriaceae species associated with oak decline in Tunisia, Linaldeddu et al reported the existence of two distinct lineages within D. corticola (i.e., A and B) [22,23]. Diplodia corticola is able to produce many bioactive secondary metabolites, which could be involved as virulence factors in host-pathogen interactions [24][25][26][27]. Considering that virulence of D. corticola is strain dependent [28], we selected three strains of D. corticola associated with holm (Q. ilex) and cork (Q. suber) oak trees exhibiting dieback symptoms and cankers in Algeria [15] to investigate the production of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of some hemisynthetic derivatives of SphA and the results of SAR studies were also discussed. 13…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of some hemisynthetic derivatives of SphA and the results of SAR studies were also discussed. 13 All the compounds, their source, biological activities and corresponding literature illustrated in the present review are reported in Tables 1 and 2 in the ESI. ‡…”
mentioning
confidence: 99%
“…It is frequently associated with dieback and canker diseases of oaks in many Mediterranean countries [ 11 , 12 , 13 ]. Among the metabolites frequently isolated from in vitro cultures of D. corticola , sphaeropsidin A is particularly promising for practical applications in agriculture and medicine due to its exciting biological properties, including antimicrobial, insecticidal, herbicidal, and anticancer activities [ 14 ]. Besides potential applications, the documented antimicrobial and insecticidal effects of sphaeropsidin A [ 15 , 16 , 17 , 18 ] are relevant for further consideration of the ecological role of the fungus.…”
Section: Introductionmentioning
confidence: 99%